ANALISIS PENGARUH MODAL MANUSIA TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Fajriyati, Aprilia; Nihayah, Annis Nurfitriana (Politeknik Negeri Ambon, 2025)
Introduction: This study investigates the impact of education, health, and population on Gross Regional Domestic Product (GRDP) per capita in the Special Region of Yogyakarta during 2015–2024. Grounded in endogenous growth theory and human capital theory, the research highlights the role of investment in education and health as key drivers of sustainable regional development.Methods: The analysis employs multiple linear regression on panel data sourced from the Central Bureau of Statistics (BPS). Education (average years of schooling), health (life expectancy), and population serve as independent variables, while GRDP per capita is used as the dependent variable.Results: Findings indicate that education and health exert a positive and significant effect on GRDP per capita, supporting the human capital framework that links better resources to higher productivity. In contrast, population growth has a negative impact, suggesting that rapid increases in population without proportional employment opportunities reduce per capita income.Conclusion and suggestion: The study concludes that education and health are vital for enhancing economic growth through human capital development, while uncontrolled population growth may hinder per capita income improvement. Therefore, policymakers should prioritize investments in education and healthcare, expand employment opportunities, and implement effective population management. Future research is recommended to include additional variables such as technological innovation, infrastructure, and institutional quality for a more comprehensive analysis of regional economic growth. Keywords: Human Capital, Education, Health, Economic Growth, Population